COMPARISON OF THE SUSCEPTIBILITY OF SIX ANTIBIOTICS AGAINST ESCHERICHIA COLI ISOLATED FROM THE CHICKEN CECUM USING THE KIRBY-BAUER DISK DIFFUSION METHOD - Meila Iscahyani; Tetty Barunawati Siagian (Buletin Veteriner Udayana, 2026)
Chicken farms often face bacterial infections, one of which is Escherichia coli. Treatment of Escherichia coli bacterial infections in chickens generally uses antibacterial agents in the form of antibiotics, to suppress the growth and spread of bacteria. Intensive use of antibiotics to prevent and treat infections can trigger resistance, which reduces the effectiveness of therapy. This study aims to evaluate the sensitivity of six types of antibiotics against E. coli isolates from 5 chicken cecum samples using the Kirby-Bauer Disk Diffusion method. Samples were taken from Chicken Farm X in Kulon Progo Regency, with the cecum collected into labeled plastic and stored in a Styrofoam box containing ice packs. Cecum samples were isolated on MacConkey agar and Nutrient Agar media. Identification was carried out based on colony morphology on MacConkey agar and bacterial colony purification on Nutrient Agar media, further confirmed by Indole testing. E. coli bacterial isolates were grown on Mueller-Hinton agar media, treated with antibiotic disks, and incubated. The inhibition zone was measured after 18 to 24 hours of incubation to assess antibiotic effectiveness. The results of the resistance test were as follows: ciprofloxacin (100%), ampicillin (80%), gentamicin (80%), tetracycline (60%), and sulfamethoxazole and trimethoprim (20%) were resistant. Factors causing resistance include the dose and duration of antibiotic administration, farm management, and regulations, supervision, and education of farmers.